The Safe Use of Sharps and Needlestick among Nurses Working in Surgical Clinics, Turkey - Zeynep Karaman Özlü; Ayşegül Çay Yayla; Kenan Gümüş; Semra Erdağı; İbrahim Özlü; Nadiye Özer; Asiye Tekin; Özgür Tuğ (Eurasian Journal of Emergency Medicine, 2016)

(untitled)
Aim: The purpose of this study was to determine the attitude of nurses working in surgical clinics regarding the safe use of sharps and towards needlestick injuries.Materials and Methods: This cross sectional descriptive study was conducted between December 2013 and February 2014 in the surgical clinics of research hospitals located in three cities within Turkey. A 54-item questionnaire consisting of 5 categories was used as the research tool. On the questionnaire was completed by 360 surgical staff nurses who agreed to participate in the study and were not on sick leave or off duty (participation rate was 88.2%).Results: The mean score obtained from nurses using the Turkish version of the “scale of medical staff’s attitude regarding the safe use of sharps and needlestick” questionnaire was 108.64±11.30. It was also determined that 46.1% of the nurses were injured 1-5 time(s) a year; 40.6% had needlestick, 32.5% were injured with broken ampoule pieces, 54.4% were vaccinated against hepatitis and tetanus; and 63.0% had knowledge about the activities of the infection control committee.Conclusions: Because of the high level of sharps and needlestick injuries, the following can be recommended: routinely conducting serological tests of the personnel routinely, change the submission of annual assessment reports into an institutional policy, and offer in-service training programs periodically.